Sustainable Economic Development and Digital Payments on Public Consumption Demand: Evidence from Indonesia - Binti Mindawati; Ris Yuwono Yudo Nugroho (Jurnal Ekonomi dan Studi Pembangunan, 2025)
The COVID-19 outbreak has influenced Indonesia's economy and prompted an investigation. The study aims to assess the impact of sustainable economic development and digital payments on household consumption demand in Indonesia. It employs consumption theory, sustainable development theory, and digital payment systems. The study's independent factors include Gross Regional Domestic Product (GRDP), population density (PD), the Human Development Index (HDI), the Environmental Quality Index (EQI), electronic money (EM), debit cards, ATMs, and credit cards. The dependent variable is household consumption demand (CD). The data consists of a combined panel of annual data from 2020 to 2023 and cross-sectional data from 33 Indonesian provinces obtained from the Bank Indonesia and Central Bureau of Statistics websites. The research takes a quantitative approach and incorporates panel data analysis techniques. The data analysis techniques utilized are the Hausman Test, Heteroskedasticity Test, Correlation Test, Pesaran's CSD Test, FGLS Test, and PCSE Test. The findings suggest that sustainable economic development, as measured by GRDP, has a favorable and significant impact on household consumption. Population density has a favorable and considerable impact on household consumption. The HDI has a large negative impact on household consumption, whereas the household EQI has a positive and significant effect. Digital payments, particularly credit cards, have a favorable and considerable effect on household consumption. Improving health and education can increase people's awareness of a healthy lifestyle, reducing their consumption of unhealthy or unnecessary goods.